2022
DOI: 10.1530/ec-22-0276
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure in children at risk of hypothalamic dysfunction

Abstract: Objective: Children with suprasellar brain damage are at risk for hypothalamic dysfunction (HD). HD may lead to decreased resting energy expenditure (REE). Decreased REE, however, is not present in all children with HD. Our aim was to assess which children suspect for HD have low REE, and its association with clinical severity of HD or radiological hypothalamic damage. Patients and methods: A retrospective cohort study was performed. Measured REE (mREE) of children at risk for HD was compared to predicted RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Recent studies have been attached increasingly importance to decreased energy expenditure in the development of HyOb. Previous studies have reported a decreased energy expenditure in patients with hypothalamic damage regardless of body composition, and this lowered energy expenditure was related with severe clinical HD ( 40 42 ). These findings help explain HyOb in our patients without excessive appetite.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent studies have been attached increasingly importance to decreased energy expenditure in the development of HyOb. Previous studies have reported a decreased energy expenditure in patients with hypothalamic damage regardless of body composition, and this lowered energy expenditure was related with severe clinical HD ( 40 42 ). These findings help explain HyOb in our patients without excessive appetite.…”
Section: Discussionmentioning
confidence: 84%
“…These findings help explain HyOb in our patients without excessive appetite. Measurement of resting energy expenditure can be useful for these patients by helping to determine whether they can benefit from therapy targeting at energy expenditure, such as dexamphetamines ( 2 , 40 ).…”
Section: Discussionmentioning
confidence: 99%